Serum calprotectin (S100A8/9): an independent predictor of ultrasound synovitis in patients with rheumatoid arthritis - Hurnakova, Jana; Zavada, Jakub; Hanova, Petra; Hulejova, Hana; Klein, Martin; Mann, Herman; Sleglova, Olga; Olejarova, Marta; Forejtova, Sarka; Ruzickova, Olga; Komarc, Martin; Vencovsky, Jiri; et al. (Arthritis research & therapy, 2015)
INTRODUCTION: Calprotectin, a heterodimeric complex of S100A8/9 (MRP8/14), has been proposed as an important serum biomarker that reflects disease activity and structural joint damage in rheumatoid arthritis (RA). The objective of this cross-sectional study was to test the hypothesis that calprotectin is associated with clinical and ultrasound-determined disease activity in patients with RA. METHODS: A total of 37 patients with RA (including 24 females, a mean disease duration of 20 months) underwent a clinical examination and 7-joint ultrasound score (German US-7) of the clinically dominant hand and foot to assess synovitis by grey-scale (GS) and synovial vascularity by power Doppler (PD) ultrasound using semiquantitative 0-3 grading. The levels of serum calprotectin and C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR) were determined at the time of the ultrasound assessment. We analysed the relationship between serum calprotectin level, traditional inflammatory markers, and ultrasound-determined synovitis. RESULTS: The levels of serum calprotectin were significantly correlated with swollen joint count (r = 0.465, p < 0.005), DAS28-ESR (r = 0.430, p < 0.01), ESR (r = 0.370, p < 0.05) and, in particular, CRP (r = 0.629, p < 0.001). Calprotectin was significantly associated with GS (r = 0.359, p < 0.05) and PD synovitis scores (r = 0.497, p < 0.005). Using multivariate regression analysis, calprotectin, adjusted for age and sex, was a better predictor of PD synovitis score (R(2) = 0.765, p < 0.001) than CRP (R(2) = 0.496, p < 0.001). CONCLUSIONS: The serum levels of calprotectin are significantly associated with clinical, laboratory and ultrasound assessments of RA disease activity. These results suggest that calprotectin might be superior to CRP for monitoring ultrasound-determined synovial inflammation in RA patients.
Keywords: krevní sedimentace; senioři; Reproducibility of Results; C-Reactive Protein; Cross-Sectional Studies; stupeň závažnosti nemoci; reprodukovatelnost výsledků; Prognosis; Predictive Value of Tests; C-reaktivní protein; Middle Aged; Sensitivity and Specificity; mužské pohlaví; prediktivní hodnota testů; Blood Sedimentation; průřezové studie; Adult; Leukocyte L1 Antigen Complex; leukocytární L1-antigenní komplex; ženské pohlaví; prognóza; ultrasonografie dopplerovská; Humans; biologické markery; Arthritis, Rheumatoid; lidé středního věku; senzitivita a specificita; Ultrasonography, Doppler; revmatoidní artritida; dospělí; Biomarkers; synovitida; Female; Aged; Severity of Illness Index; Synovitis; lidé; Male